PENGAMATA PENEBANGAN DAN PENGANGKUTAN SAGU DI DESA TANJUNG KECAMATAN TEBING TINGGI PROPSI RIAU - Wesman Endom (Jurnal Penelitian Hasil Hutan, 1992)
ln  indonesia  Sago  (Metroxylon sp)  is one  of  the  natural  resources   which  is potenlally  great   enaugh for  developing  national income.  The   areas   distribute over  many  places  particularly  in Irian.  Jaya,    Maluku, some parts  of  Sulawesi,    Kalimantan and Sumatera, covering  ± 6 00  000 ha.In Sumatera, sago grow in swampy area like South Sumatera, Jambi, Riau and Aceh.  ln Riau the most famous producer sago area is Sab Districl of  Tebing   Tinggi of District Bengkalis .  According  to the last report  of 1989,  the total sago area in Sub District of Tebing tinggi  is± 15 915 ha,  and has producted sago of 156  500 ton.This paper  discussing same aspects of technical harvesting of sago.  which has preliminary observed in an area  of the  farmer  as one of the sharing sago cooperation of Harmonis,  that  localed  in Desa Tanjung. Sub District of Tebing Tinggi. Those aspects   were felling, toping and branching and tranportalion with and addition of sago proccesing.                                                         The resul: showed that felling  topping and branching and sago tranportation are carried out by group of felling  operation  wkich is consist of 6-8 men/group. the salary system is done by contract.The sagos are felled before  flowering  and each trees was cut  wilh diameter ranged.from 49-64 cm and need ±   16,1 minutes/tree.the log then cutted after lopping and branching into 8-11 pieces depend   on the  tog length  1, 05-1 ,25 m/pieces.  This pieces   are   called tual. Each  tual  then hauled   using  manual  system  as  well as  "nglebek"   on  a rail system  of the  wood.   In average to haul  of  the  distance ± 400 in from the felling   site  to sago industry   was ±  30 minutes.The sago processing    covered some  aclivities    of burking,   slicing   and flouring need±  4,5  minutes  per   tual.  Therefore   plus other delayed  time  with  calculation  10  tual/tree, the total  processing   of one  tree  sago  need  1 hour.  The productivity   of man  power   is able  to finish  of sago  horvesting  ±  1  tree/man.    Using  the wage  of Rp.  400/tual,   therefore  the total salary is Rp,  4000/day.